Faktor Penyebab Pengguna Narkotika di Kalangan Masyarakat - Oktir Nebi (Universitas Batanghari Jambi, 2019)
Drug abuse also affects the body and mental-emotional of its users. If it is consumed more often, especially in excess amounts it will damage the health of the body, psyche and social functions in the community. The influence of drugs on adolescents can even have more fatal consequences, because it inhibits his personality development. Narcotics can damage one's potential, because it is considered a